2015
DOI: 10.3906/zoo-1406-6
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the population parameters of freshwater crayfish(Astacus leptodactylus Esch., 1823) in Lake İznik (Bursa)

Abstract: Although crayfish are not much consumed in Turkey, fishing of the freshwater crayfish, which are especially sought after in European countries, started in lakes Manyas and Apolyont (Uluabat) at the beginning of 1965. It gained importance with its increasing export volume (Berber and Balık, 2006). Statistics for the number of freshwater crayfish caught in Turkish inland waters were not routinely recorded until 1976, and the number of freshwater crayfish caught was given as 3.885 t for the first time in 1977 (TÜ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The mean value of condition factor for all individuals in the present study was found to be 2.58±0.29 which being very close to unity, indicates that the A. leptodactylus is in good condition. Similarly, Aydın et al [14] recorded a mean condition factor value of 2.6 for A. leptodactylus in İznik Lake. Also, Kaya [22] reported the value of the mean condition factor to be 3.31 for A. leptodactylus in Eğirdir Lake for all individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean value of condition factor for all individuals in the present study was found to be 2.58±0.29 which being very close to unity, indicates that the A. leptodactylus is in good condition. Similarly, Aydın et al [14] recorded a mean condition factor value of 2.6 for A. leptodactylus in İznik Lake. Also, Kaya [22] reported the value of the mean condition factor to be 3.31 for A. leptodactylus in Eğirdir Lake for all individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In general, while the body weight of the male individuals of crayfish is greater, and their walking legs and their cheliped wider and longer, the females have a wider and longer abdomen [14]. It has been found in most of the studies done on A. leptodactylus in Turkey that due to the size of their walking legs and their weight, male individuals have a greater average length and weight compared to female individuals [14][15][16]. Similarly, the mean values that have turned out to be higher for the male population are carapace length, carapace width, abdomen length, abdomen width, cheliped length, cheliped width, total length, total weight and condition factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Lake Gıcı, it was determined as 3.11 in all individuals, 2.75 in females and 3.36 in males. Aydın et al [14] found the condition factor to be 2.6 in freshwater lobsters, 3.33 in male lobsters, 3.15 in females and 3.23 in all individuals. Condition factor is defined as one of the nutrition and development criteria in which the morphological structure is best controlled in lobsters by Kaya [15] .…”
Section: Dıscussıon and Conclusıonmentioning
confidence: 99%
“…Deniz (Bök), Harlıoğlu, and Deval (2010) and Deniz (Bök), Aydın, and Ateş (2013) investigated morphological characteristics of A. leptodactylus. Aydin, Harlıoğlu, and Deniz (2015) investigated biological and population characteristics of A. leptodactylus. However, there is no direct study on rice.…”
Section: Introductionmentioning
confidence: 99%